Seroprevelence of rubella among children suspected of having measles in Gadarif Hospital, Eastern Sudan - Ahmed, Mohammed Ahmed A. (Sudan J Paediatr, 2019)
While generally mild in children, rubella infection during pregnancy can lead to miscarriage, foetal death or congenital rubella syndrome. Rubella vaccination is not yet available as a part of routine immunisation in Sudan, and the burden of infection is unknown. Using the clinical case definition adopted by the World Health Organisation, a total of 123 children suspected of having of measles were enrolled in this study during January–December 2017 in Gadarif Hospital, Eastern Sudan. Those cases whose sera were negative for measles IgM antibodies were tested for rubella IgM antibody. A confirmed rubella case was a person who tested positive for rubella IgM. Sera were analysed for IgM specific antibodies against measles virus and rubella virus using enzyme-linked immunosorbent assay. Among the total 123 children suspected to have measles, 92 (74.8%) children were positive for measles IgM antibodies. Of the 31 children who had measles IgM antibodies negative, 20 (16.3%) children were seropositive for rubella IgM antibodies. Implementation of a surveillance system will provide the improved estimates of rubella virus and estimated the burden of congenital rubella syndrome. Such information is necessary and it is an important step for future policy decisions for vaccine delivery strategies.